2008
DOI: 10.1073/pnas.0711625105
|View full text |Cite
|
Sign up to set email alerts
|

A phosphopantetheinylating polyketide synthase producing a linear polyene to initiate enediyne antitumor antibiotic biosynthesis

Abstract: The enediynes, unified by their unique molecular architecture and mode of action, represent some of the most potent anticancer drugs ever discovered. The biosynthesis of the enediyne core has been predicted to be initiated by a polyketide synthase (PKS) that is distinct from all known PKSs. Characterization of the enediyne PKS involved in C-1027 (SgcE) and neocarzinostatin (NcsE) biosynthesis has now revealed that (i) the PKSs contain a central acyl carrier protein domain and C-terminal phosphopantetheinyl tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
137
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 54 publications
5
137
1
4
Order By: Relevance
“…Thus, the phylogenetic divergence between 9-and 10-membered PKSEs may reflect enediyne core-specific protein-protein interactions between the PKSE and corresponding accessory enzymes. This hypothesis is consistent with our earlier observation that only the 9-membered pksE genes, but not calE8, could restore C-1027 or NCS production in pksE null mutants (15). As an important first step toward elucidating pathway-directing interactions between PKSEs and accessory enzymes, we demonstrated the production of 1 by all possible PKSE-TE combinations.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Thus, the phylogenetic divergence between 9-and 10-membered PKSEs may reflect enediyne core-specific protein-protein interactions between the PKSE and corresponding accessory enzymes. This hypothesis is consistent with our earlier observation that only the 9-membered pksE genes, but not calE8, could restore C-1027 or NCS production in pksE null mutants (15). As an important first step toward elucidating pathway-directing interactions between PKSEs and accessory enzymes, we demonstrated the production of 1 by all possible PKSE-TE combinations.…”
Section: Resultssupporting
confidence: 78%
“…S2) and expected mass of 198.1 and confirmed to be identical to the previously characterized authentic standard (15). Productions of 1 by either the 9-or 10-membered PKSE-TE systems under the conditions examined are very similar as exemplified by the estimated yields of 1 at 1.3 AE 0.5 mg∕L for CalE8-CalE7 and 2.8 AE 1.0 mg∕L for MdpE-MdpE10, respectively.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Comparative analysis showed that ACPS-type PPTases usually contain about 120 amino acids carrying motif P2 [(V/I)G(V/I)D] and motif P3 [(F/W)(S/C/T/)xKE(A/S)xxK] (Lambalot et al 1996), whereas the Sfp-type PPTases contain about 220 amino acids with motifs P2 and P3 plus motif P1 [PxWPxGxxGS(M/L)THCxGY] (Sanchez et al 2001). The third type of PPTases is fused with fatty acid synthases or polyketide synthases as a functional domain (Murugan and Liang 2008;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%